2018
DOI: 10.1186/s13104-018-4024-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lyssavirus antigen and antibody levels among apparently healthy and suspected rabid dogs in South-Eastern Nigeria

Abstract: ObjectivesDomestic dogs are the main reservoir of rabies virus (RABV) infection in Nigeria, thus surveillance of rabies in dog populations is crucial in order to understand the patterns of spread of infection and ultimately devise an appropriate rabies control strategy. This study determined the presence of lyssavirus antigen in brain tissues and anti-rabies antibodies in sera of apparently healthy and suspected-rabid dogs slaughtered for human consumption at local markets in South-Eastern Nigeria.ResultsOur f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…1 , Supplementary Table 4 ). A group of 73 articles corresponding to 142 incidence data was finally selected for this review [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , ...…”
Section: Resultsunclassified
See 2 more Smart Citations
“…1 , Supplementary Table 4 ). A group of 73 articles corresponding to 142 incidence data was finally selected for this review [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , ...…”
Section: Resultsunclassified
“…The 40 articles (42 incidence data) in dogs with active infection ( N = 15,600 participants) reported incidence ranging from 0 to 100% with a meta-incidence of 44.1% (95% CI: 35.1–53.4) ( Fig. 4 ) [ 18 , [20] , [21] , [22] , 25 , 28 , 33 , 36 , 40 , 41 , 43 , [45] , [46] , [47] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , 59 , 61 , 62 , 65 , 66 , 70 , 75 , 76 , 78 , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , 89 , 90 ]. RABV meta-incidence in dogs with evidence of active RABV infection ranged from 0% in wild dogs to 86.3% in suspected rabid stray dogs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although clinical data are not available for these culled dogs, this proportion is similar to that in found-dead dogs in rabies endemic regions [ 25 ] but higher than that previously reported for apparently healthy dogs in other endemic regions. For example, a maximum of 5% positive was demonstrated in Nigeria, and researchers could not confirm the health status of the animals [ 26 ]. The reason for the apparently high proportion of rabid dogs among the culled sample is not known but culling process may have been biased toward aggressive or sick dogs.…”
Section: Discussionmentioning
confidence: 99%
“…8 Another study observed an inverse relationship between the presence of lyssavirus antigens and levels of rabies antibodies in unvaccinated dogs that underscores the notion of immune evasion following lyssavirus infection. 9 In another study by Vaughn et al 10 , thirteen groups totaling 117 dogs were inoculated with the rabies virus and 54 dogs developed fatal rabies (49%) pointing out abortive clinical infection after actual virus inoculation.…”
mentioning
confidence: 97%